Alphaworld: stay away - Feely, Jenny (Oxford University Press Melbourne, 2004)
"Stay Away" is a part of the Alphaworld series, which typically blends elements of fantasy and adventure with themes of personal growth and relationships. In this book, readers can expect an engaging storyline that explores the dynamics of power, loyalty, and the struggles faced by characters in a richly built world. The narrative often intertwines action with deeper emotional arcs, making it appealing to fans of both fantasy and character-driven tales.